Potential tactics with vitamin D and certain phytochemicals for enhancing the effectiveness of immune-checkpoint blockade therapies - Ai Tsuji; Sayuri Yoshikawa; Sae Morikawa; Yuka Ikeda; Kurumi Taniguchi; Haruka Sawamura; Tomoko Asai; Satoru Matsuda (Open Exploration Publishing Inc., 2023)
Immunotherapy strategies targeting immune checkpoint molecules such as programmed cell death-1 (PD-1) and cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) are revolutionizing oncology. However, its effectiveness is limited in part due to the loss of effector cytotoxic T lymphocytes. Interestingly, supplementation of vitamin D could abolish the repressive effect of programmed cell death-ligand 1 (PD-L1) on CD8+ T cells, which might prevent the lymphocytopenia. In addition, vitamin D signaling could contribute to the differentiation of T-regulatory (Treg) cells associated with the expression of Treg markers such as forkhead box P3 (FOXP3) and CTLA-4. Furthermore, vitamin D may be associated with the stimulation of innate immunity. Peroxisome proliferator-activated receptor (PPAR) and estrogen receptor (ESR) signaling, and even the signaling from phosphoinositide-3 kinase (PI3K)/AKT pathway could have inhibitory roles in carcinogenesis possibly via the modulation of immune checkpoint molecules. In some cases, certain small molecules including vitamin D could be a novel therapeutic modality with a promising potential for the better performance of immune checkpoint blockade cancer therapies.